Ethnomathematics: Uncovering Mathematical Patterns in the Barter Tradition of Tempu at the KAMU Market - Ulfa Annisa Lubis; Israq Maharani; Jihan Hidayah Putri (OMEGA: Jurnal Keilmuan Pendidikan Matematika, 2026)
Ethnomathematics is a field of study that examines the relationship between culture and mathematics. This research aims to uncover the mathematical patterns found in the barter tradition using Tempu as a medium of exchange at the KAMU Market. The method used is qualitative research with an ethnographic approach. Data were collected through direct observation, interviews, and documentation. The results show that, physically, all Tempu units have a uniform shape and size with a mutually agreed standard exchange value, where one piece of Tempu is worth Rp2,000.00. In its transactional practices, various implicit mathematical applications were found, namely basic multiplication operations, concepts of comparison and ratio, as well as an understanding of units and value standardization. This mathematical knowledge is formed from local wisdom and has become a part of the community's daily life without being consciously recognized as formal mathematics. The conclusion of this study is that the Tempu barter tradition contains rich ethnomathematical values and can be used as a contextual source for learning mathematics while preserving local culture.